Data from: Life in the fat lane: seasonal regulation of insulin sensitivity, food intake, and adipose biology in brown bears - Rigano, Kimberly S.; Gehring, Jamie L.; Evans Hutzenbiler, Brandon D.; Chen, Annie V.; Nelson, O. Lynne; Vella, Chantal A.; Robbins, Charles T.; Jansen, Heiko T. (Zenodo, 2016)
Grizzly bears (Ursus arctos horribilis) have evolved remarkable metabolic adaptations including enormous fat accumulation during the active season followed by fasting during hibernation. However, these fluctuations in body mass do not cause the same harmful effects associated with obesity in humans. To better understand these seasonal transitions, we performed insulin and glucose tolerance tests in captive grizzly bears, characterized the annual profiles of circulating adipokines, and tested the anorectic effects of centrally administered leptin at different times of the year. We also used bear gluteal adipocyte cultures to test insulin and beta-adrenergic sensitivity in vitro. Bears were insulin resistant during hibernation but were sensitive during the spring and fall active periods. Hibernating bears remained euglycemic, possibly due to hyperinsulinemia and hyperglucagonemia. Adipokine concentrations were relatively low throughout the active season but peaked in mid-October prior to hibernation when fat content was greatest. Serum glycerol was highest during hibernation, indicating ongoing lipolysis. Centrally administered leptin reduced food intake in October, but not in August, revealing seasonal variation in the brain's sensitivity to its anorectic effects. This was supported by strong phosphorylated signal transducer and activator of transcription 3 labeling within the hypothalamus of hibernating bears; labeling virtually disappeared in active bears. Adipocytes collected during hibernation were insulin resistant when cultured with hibernation serum but became sensitive when cultured with active season serum. Heat treatment of active serum blocked much of this action. Clarifying the cellular mechanisms responsible for the physiology of hibernating bears may inform new treatments for metabolic disorders. Data to accompany Rigano et. al. (2016) J.Comp.Physiol, B data to accompany manuscript Rigano_etal_JCPB_2016.zip